2020
DOI: 10.1177/0266242620965384
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between financial distress and well-being: Exploring the role of self-employment

Abstract: This article investigate the relationship between financial distress, well-being and employment status. Using several indicators of financial distress and of well-being, our econometric analysis shows that the negative association between financial distress and well-being is moderated by employment status in the sense that financial problems are more strongly associated with poor well-being for the self-employed compared to the wage-employed. Hence, when self-employed workers find themselves in a situation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 65 publications
(67 reference statements)
0
13
0
Order By: Relevance
“…For example, analyses with UK data reveal that financial worries during the pandemic increased mental distress and reduced the well-being benefits of self-employment [ 75 ]. Evidence from older individuals in 20 European countries and Israel shows that self-employed workers who experience financial distress suffer more pronounced reductions in life satisfaction than salaried workers [ 76 ].…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
“…For example, analyses with UK data reveal that financial worries during the pandemic increased mental distress and reduced the well-being benefits of self-employment [ 75 ]. Evidence from older individuals in 20 European countries and Israel shows that self-employed workers who experience financial distress suffer more pronounced reductions in life satisfaction than salaried workers [ 76 ].…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
“…In case of financial distress of self-employed workers, the negative consequences for their well-being were more severe. This was typical for the self-employed with and without employees (Berrill et al, 2020). Further research has confirmed that job mobility rate and wages decrease could result in a complex interaction among savings, wages, mobility, and debt.…”
Section: Empirical Findings and Discussionmentioning
confidence: 63%
“…Interestingly, financial stress significantly and positively affects the financial well-being of the respondents. Generally, financial stress weakens financial well-being and negatively affects well-being (Berrill et al, 2021).…”
Section: Discussionmentioning
confidence: 99%